Sierra Leone : Third and Fourth Reviews Under the Extended Credit Facility Arrangement and Financing Assurances Review, Requests for Waivers for Nonobservance of Performance Criteria and Modification of Performance Criteria, and Requests for Rephasing and Augmentation of Access Under the Extended Credit Facility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses Sierra Leone's Third and Fourth Reviews Under the Extended Credit Facility Arrangement and Financing Assurances Review, Requests for Waivers for Nonobservance of Performance Criteria (PC) and Modification of PC. Program implementation has been good, notwithstanding the shocks that the economy has experienced. Despite missing several end-2014 PCs, owing to the Ebola outbreak, authorities have placed policies back on track. All end-June 2015 PCs, as well as most structural benchmarks, have been observed. The IMF staff supports the authorities' requests for waivers, as well as for additional financing from the IMF.